The Neotropical Orb-Weaver Genera Epeiroides, Bertrana and Amazonepeira (Araneae: Araneidae). - Herbert W. Levi (Psyche: A Journal of Entomology)
Most Neotropical spider specimens preserved in museums were collected by ornithologists, entomologists or amateur naturalists, who picked up spiders when their preferred organisms could not be found. Invariably such collectors bring back the biggest, showiest spiders. Only in recent years have arachnologists themselves collected, concentrating on the less conspicuous but often more interesting spiders that previously were overlooked. Tiny spiders frequently show greater diversity in structure than larger ones, and have more species in the Holarctic region. At present we know much less about the minute Neotropical Araneidae than about the larger species.